PERENCANAAN PAJAK DENGAN PEMBERIAN NATURA KEPADA PEGAWAI PERUSAHAAN SEBAGAI UPAYA UNTUK MENGEFISIENSIKAN PAJAK PADA PT. BANK SULUT GO - Johanis, Astrid S.; Nangoi, Grace B.; Tirayoh, Victorina Z. (JURNAL RISET AKUNTANSI GOING CONCERN, 2018)
Tax is one of the largest sourcesof income the country uses to finance household expenses and needs. Tax became one of the foundations of the state revenue sector in order to ensure the sustainability of national development financing. And for the business world one of the problems that compaines often encounter is tax. Therefore, companies need a way that can Streamline tax burden, and one way can be done with tax planning. The purpose of this study is to know the tax planning by giving natura to company employees can efficient tax burden on the company. And in this research object which become research place that is PT. Bank SULUT GO. Where PT. Bank SULUT GO become one of the companies that apply this way and in this case the company chose giving natura to its employees as an effort in tax planning. Research method in this research is descriptive. The data in this study was obtained through interviews and documentation. The results showed that tax planning by giving natura can efficient tax burden on PT. Bank SULUT GO.Keywords :Tax Planning, Giving Natura